PERAN PENAMBAHAN GAYA KEPEMIMPINAN TRANSFORMASIONAL PADA GAYA KEPEMIMPINAN TRANSAKSIONAL DALAM MEMPREDIKSI KINERJA, ORGANIZATIONAL CITIZENSHIP BEHAVIOR DAN SIKAP BAWAHAN TERHADAP ATASAN: STUDI EMPIRIS PADA PERUSAHAAN PETERNAKAN - Mayasari, Desi; Syahlani, Suci Paramitasari (Universitas Muhammadiyah Surakarta, 2010)
This study aims to measure the influence of transformational leadership style on performance, organizational citizenship behavior, and subordinates attitude toward the leader. The research design used in this study is survey. Respondents of this research were 140 subordinates that worked in three companies in livestock industry that has international and national market share. Random sampling was use to determine the respondents based on employee list. Data was analyzed by simple linear regression analysis and multiple linear regression analysis. The results of the analysis show that there is an increase explanation capability aplication of transformational leadership addition on transactional leadership to performance, organizational citizenship behavior, subordinates attitude towards the each leader were 2,3%, 8,3%, and 70,4% respectively. The results of this research lead to the conclusion that transformasional leadership addition gave stronger explanation of transactional leadership capability to predict performance, organizational citizenship behavior, and subordinates attitude towards the leader. As many as 17.1% variability of performance could be explained by addition transformational leadership on transactional leadership, while it was 12,3% dan 72,4% on variability of organizational citizenship behavior and attitude of subordinates respectively.